Pengembangan Mobile Aplikasi Resep Makanan Indonesia Serta Monitoring Kalori Dan Nutrisi Harian Berbasis Android - Risma Ekawati; Onki Alexander; Untung Suprihadi (STMIK IKMI Cirebon, 2021)
The benefits of an Android-based application make mobile application software developers improve the quality of their applications, one of which is implementing this android application to find out food recipe information and monitor daily calorie nutrition for users in consuming food as well as maintaining health. Researchers see the potential of an Android-based daily calorie monitoring application applied to the community, one of which focuses on housewives. This study aims to develop an Android-based food recipe application system into food recipes that also displays the daily calorie and nutritional content of food. This application can combine the best things from mobile applications with the features that Android Studio already has. The benefits of this research can be recommended or referenced for the Unitary State of the Republic of Indonesia in developing mobile applications that are more optimal for the needs of the community. Development in this system applies the waterfall method by completing the initial stage before continuing the next stage. Unified Modeling Language (UML) for system design. Testing this application using the Black Box, this application can carry out its functions properly, efficiently and testing this application has been correct and has no errors both in terms of logic and function and is feasible to implement. Meanwhile, from the results of the questionnaire, respondents said they agreed with this calorie adequacy monitoring application. The ability of the application software created can also be opened with the Android OS version and can be run online or offline.